Distinct cytokine profiles in malaria coinfections: A systematic review - Manas Kotepui; Wanida Mala; Pattamaporn Kwankaew; Kwuntida Uthaisar Kotepui; Frederick Ramirez Masangkay; Polrat Wilairatana (PLoS Neglected Tropical Diseases, 2023)
Background Few data exist on the distinct cytokine profiles of individuals with malaria coinfections and other diseases. This study focuses on data collation of distinct cytokine profiles between individuals with malaria coinfections and monoinfections to provide evidence for further diagnostic or prognostic studies. Methods We searched five medical databases, including Embase, MEDLINE, PubMed, Ovid, and Scopus, for articles on cytokines in malaria coinfections published from January 1, 1983 to May 3, 2022, after which the distinct cytokine patterns between malaria coinfection and monoinfection were illustrated in heat maps. Results Preliminary searches identified 2127 articles, of which 34 were included in the systematic review. Distinct cytokine profiles in malaria coinfections with bacteremia; HIV; HBV; dengue; filariasis; intestinal parasites; and schistosomiasis were tumor necrosis factor (TNF), interferon (IFN)-γ, IFN-α, interleukin (IL)-1, IL-1 receptor antagonist (Ra), IL-4, IL-7, IL-12, IL-15, IL-17; TNF, IL-1Ra, IL-4, IL-10, IL-12, IL-18, CCL3, CCL5, CXCL8, CXCL9, CXCL11, granulocyte colony-stimulating factor (G-CSF); TNF, IFN-γ, IL-4, IL-6, IL-10, IL-12, CCL2; IFN-γ, IL-1, IL-4, IL-6, IL-10, IL-12, IL-13, IL-17, CCL2, CCL3, CCL4, G-CSF; IL-1Ra, IL-10, CXCL5, CXCL8, CXCL10; TNF, IL-2, IL-4, IL-6, IL-10; and TNF, IFN-γ, IL-4, IL-5, IL-10, transforming growth factor-β, CXCL8, respectively. Conclusion This systematic review provides information on distinct cytokine profiles of malaria coinfections and malaria monoinfections. Further studies should investigate whether specific cytokines for each coinfection type could serve as essential diagnostic or prognostic biomarkers for malaria coinfections. Author summary Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, Plasmodium ovale, and Plasmodium knowlesi infections all cause malaria, an acute febrile illness that is transmitted to people by the bites of infected female Anopheles mosquitoes. Following malaria infections in people, an individual’s immune responses are produced against the infection, leading to various clinical outcomes. The immune responses included groups of cytokines, small proteins that are secreted by immune system cells to help the body’s immune responses against infections. In malaria-endemic areas, malaria can coinfect with other several diseases as they have overlapping geographical distributions. Malaria coinfections with other diseases may lead to distinct cytokine production in infected patients. We, therefore, aimed to synthesize distinct cytokine profiles of individuals with malaria coinfections using a systematic review of the literature to provide insights into the current status of cytokine studies and identify research gaps. Based on the results of 34 studies, we synthesized that there were distinct cytokine profiles in malaria coinfections with bacteremia, intestinal parasites, and viruses. This information would provide the baseline data for further studies to investigate specific cytokines for each coinfection type that could serve as essential diagnostic or prognostic biomarkers for malaria coinfections.